Cuddly animals - Gardner,Charlie (Great Britain: Dorling Kindersley, 2011)
Introduce your baby to cute cuddly animals with touch and feel textures. Tickle and touch the textures together with your baby and help them discover all about Cuddly Animals . Let their little hands roam to find a shaggy-haired pony, a fluffy lion cub and a fuzzy-tailed bushbaby
Keywords: Animals Pictorial works Juvenile literature